Pulsed current-voltage electrodeposition of stoichiometric Bi2Te3 nanowires and their crystallographic characterization by transmission electron backscatter diffraction. Issue 1 (31st December 2019) - Manzano, Cristina V.; Polyakov, Mikhail N.; Maiz, Jon; Aguirre, Myriam H.; Maeder, Xavier; Martín-González, Marisol
ABSTRACT: Bi2 Te3 nanowires with diameters ranging from 25 to 270 nm, ultra-high aspect ratio, and uniform growth front were fabricated by electrodeposition, pulsing between zero current density during the off time and constant potential during the on time (pulsed-current-voltage method, p-IV). The use of zero current density during the off time is to ensure no electrodeposition is carried out and the system is totally relaxed. By this procedure, stoichiometric nanowires oriented perpendicular to the c-axis is obtained for the different diameters of porous alumina templates. In addition, the samples show a uniform growth front with ultra-high aspect ratio single crystal nanowires. The high degree of crystallinity was verified by transmission electron backscatter diffraction. This characterization revealed that the nanowires present both large single crystalline areas and areas with alternating twin configurations. Graphical Abstract: uf0001